The Status Of Wind Resource Assessment(Wra) Techniques, Wind Energy Potential and Utilisation In Malaysia and Other Countries - Lawan, S.M; Abidin, W.A.W.Z; Chai, W.Y; Baharun, A.; Masri, T. (Asian Research Publishing Network (ARPN, 2013)
Current dependency on finite reserves fossil fuels and adverse environmental effects of conventional power system created new dimension interest in renewable energy sources toward building a sustainable and reliable energy in the near future. Wind energy is renewable and considered as one of the safest, cleanest and fastest growing forms of renewable energy in the world. Generation of electrical energy from wind can only be possible where there is considerable wind resource exists. For this reasons an accurate wind resource evaluation is a vital tool for harnessing energy content in a wind. This paper is critically reviews different techniques used in wind resource assessment, prospects and challenges of utilizing wind energy in some developed and developing countries; however recent progress and development of wind energy potential and utilizations in the countries neighboring Malaysia are discussed. Several recent wind energy potential studies, areas that are suitable for exploitation of wind energy for electrical power generation as well as the current situation of wind energy utilization in Malaysia and possible recommendations were presented.